2008
DOI: 10.1111/j.1551-2916.2008.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

State of the Dispersant and Particle Surface During Wet‐Jet Milling for Preparation of a Stable Slurry

Abstract: Wet‐jet‐milled alumina slurries exhibited distinctly different stability behavior compared with ball‐milled ones in terms of reflocculent efficiency and rheological properties. The distinction was attributed to the different behavior of the same dispersant (NH4+ salt of poly(acrylic acid); PAA–NH4+) in ball milling and wet‐jet milling. Alumina particles after the wet‐jet milling retained the initial surface conditions, although ball‐milled alumina particles yielded more hydroxyl groups on the surface. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Some isolated polycrystalline nanometric agglomerates were also observed in these powders (Figure 3(f)) but were absent in the powder milled under acidic pH condition. Similar coatings of low density aluminum trihydroxides were also observed in ball milled -alumina powders in other studies [33][34][35]. These results confirm that hydration occurs on the surface of alumina particles, in a process that is intensified under milling.…”
Section: Starting and Milled Powderssupporting
confidence: 88%
“…Some isolated polycrystalline nanometric agglomerates were also observed in these powders (Figure 3(f)) but were absent in the powder milled under acidic pH condition. Similar coatings of low density aluminum trihydroxides were also observed in ball milled -alumina powders in other studies [33][34][35]. These results confirm that hydration occurs on the surface of alumina particles, in a process that is intensified under milling.…”
Section: Starting and Milled Powderssupporting
confidence: 88%
“…reported that microfluidization enhances the electrostatic repulsion between the particles without degrading the dispersant or the particle surface and enhances the steric repulsion by increasing the average polymer molecular weight and length, which increases the interparticle distance and slurry stability [20]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, most studies in the field of ceramic processing have not specifically investigated the microfluidization process. Limited studies of Al 2 O 3 and ZnO using wet-jet milling were conducted by only one research group of AIST in Japan [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cavitation, turbulent and shear flow are induced at high speeds. In our previous works, it has been demonstrated that the wet-jet milled suspensions exhibited distinctly different stability behavior as compared to ball-milled ones in terms of reflocculation efficiency and rheological properties [18,19]. Furthermore, the authors also showed that the surface of wet-jet milled particles was not damaged because the given collision energy during wet-jet milling was significantly smaller than that of during ball milling [18].…”
Section: Introductionmentioning
confidence: 90%